2021
DOI: 10.21203/rs.3.rs-422225/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Risk factors for the diagnosis of colorectal cancer

Abstract: Background: Colorectal cancer (CRC), defined as cancer of the colon or rectum, is one of the most frequently diagnosed cancers, and, according to the World Health Organisation database GLOBOCAN, it accounts for about 1.4 million new diagnoses annually worldwide. There is an association between the occurrence of colorectal cancer and non-modifiable risk factors, including age and hereditary factors, as well as with modifiable factors linked to the environment and lifestyle choices.Methods: The study included 80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…In the USA, alcohol consumption and smoking result in a one in five probability of CRC. 10 The risk increases with an increase in BMI with obese individuals having a higher risk. Compared to individuals with a BMI of 23, elderly individuals tend to have a 5–100% higher risk of CRC with a BMI of 30.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the USA, alcohol consumption and smoking result in a one in five probability of CRC. 10 The risk increases with an increase in BMI with obese individuals having a higher risk. Compared to individuals with a BMI of 23, elderly individuals tend to have a 5–100% higher risk of CRC with a BMI of 30.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to individuals with a BMI of 23, elderly individuals tend to have a 5–100% higher risk of CRC with a BMI of 30. 10 …”
Section: Introductionmentioning
confidence: 99%
“…González et al [32] reported that colorectal cancer cases were increasing rapidly and that early diagnosis was very important to prevent the rapid increase in cancer cases and mortality rates. Lewandowska et al [33] emphasized that a sedentary lifestyle was an important risk factor for colorectal cancer. Our study is in parallel with the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Being acquainted with this disease due to the previous history of colorectal cancer in another relative may lead to the concern of "I wonder if it is my turn" inpatient relatives. In the study conducted by Şentürk et al [34], it was reported that symptoms such as anxiety, depressive mood, and stress increased signi cantly in patients and their relatives during the cancer diagnosis process [33]. In the study of Erdoğan et al [35] it was determined that individuals caring for patients had concerns and doubts about the future, were not strong enough to x some situations, and experienced feelings such as fear, anxiety, sadness, stress, depression, and insecurity, and that the stress they experienced through medical treatments increased the mortality rate of caregivers in 5 years [35].…”
Section: Discussionmentioning
confidence: 99%
“…Colorectal cancer (CRC) is the third most common cancer worldwide and the lifetime risk of developing CRC is nearly 4% in all populations (1,2). The tumorigenesis and progression of CRC arise from different causes such as genetic instability, dysregulated genes (both tumor suppressors and oncogenes), and non-coding RNAs (microRNAs and long non-coding RNAs), the activation and inactivation of signaling pathways involved in tumorigenesis, as well as microenvironment (3,4).…”
Section: Introductionmentioning
confidence: 99%